Explore a sustainable development education (ESD) framework of planting and environmental design based on the barriers of knowledge dissemination between academia and practice - Xiwei Shen; Yiwei Huang; Phillip Zawarus; Jie Kong; Qiuyi Yang; Ling Wang (Journal of Asian Architecture and Building Engineering, 2025)
Landscape architecture education in the 21st century witnessed a transition from merely art and engineering to a future that integrates knowledge in science, psychology, environmental studies, ecology, and more. Using planting and environmental design practice as an example, the education focus needs to shift from purely demonstrating aesthetics to a comprehensive framework that integrates aesthetics, ecological services, and social and spatial functionality. This paper explored the gaps in planting and environmental design between pedagogy and practice. The result indicates that college-level education in planting and environmental design is majorly focused on plant identification, ornamental properties, and construction drawing communications, whereas the practical field indicates an expectation of more horticultural and ecological knowledge in design practice from college-level education. To bridge the gap, the article identified the proper trajectories through qualitative research including a questionnaire survey, semi-structured interview, content analysis and cross analysis to explore a sustainable development education framework of planting and environmental design based on the barriers of knowledge dissemination between academia and practice.